Caracterização do lenho de árvores de clones de Eucalyptus urophylla x Eucalyptus grandis em áreas sujeitas a danos por ventos - Braz, Rafael Leite (2011)
Forest plantations in the Vale do Rio Doce in Minas Gerais have suffered damage caused by the action of wind, especially in areas of lowlands and in young stands. Studies to identify relationships between the susceptibility of trees of the wood properties are of great importance, allowing selection of clones more tolerant to wind action. Thus, the purpose of this study was to characterize the wood of trees of ten clones of the hybrid Eucalyptus urophylla x Eucalyptus grandis, 30 and 35 months of age, on the strength of the tree to fall and the anatomical, physical, mechanical and chemical characteristics of trees. The study site was in lowland regions, where trees are more vulnerable and prone to damage from winds with altitude near 250 m and with low intensity of the climatological winds and frequent occurrence of micro-atmospheric explosions. For this, the dendometric characteristics of the trees were measured and evaluated and strength tests of the tree to fall were done, simulating the effect of wind and a non-destructive method for the determination of longitudinal residual strain. In the laboratory sample of wood were prepared and then analyzed the quantitative anatomical parameters of wood, for the vessels and the morphology of the fibers, the density, the bending, the concentrations of extractives, lignin and holocellulose and calculated the growth stress. The conclusion is that the clone CNB017 showed the best results, especially in the testing of breaking strength, the physical and mechanical properties evaluated. For the chemical composition, the clones showed close values for the levels of extractive, lignin and holocellulose, serving only as indicative for the production and yield of cellulose. The endurance test and the mechanical and physical characteristics stood out as the most suitable parameters for the assessment and classification of clones susceptible to wind action, whereas the clones that showed the best results were common. However there is need to broaden the base information regarding the susceptibility of trees to wind